Personalized treatment approach to gastroenteropancreatic neuroendocrine tumors: a medical oncologist's perspective. Issue 9 (September 2016) - Paul, Davinder; Ostwal, Vikas; Bose, Subhadeep; Basu, Sandip; Gupta, Sudeep
Abstract : The medical management of gastroenteropancreatic neuroendocrine tumors involves treatment of symptomatic disease related to hormone secretions or bulky unresectable metastatic disease. Combining gallium DOTA with fluorine-18 fluorodeoxyglucose-PET along with histopathological grading helps to determine tumor heterogeneity and seek reasons for poor response to therapy. In the light of adding chemotherapy in selected patients with intermediate-grade tumors, the newer scan helps in personalization of the therapy along with the biopsy. The tumor dedifferentiation over the particular time period leading to aggressive behavior, a well-known entity, is contrasted with the redifferentiation phenomenon in some patients as a result of chemotherapy or targeted drug therapy. This may support the basis for combining peptide receptor-targeted radiotherapy/octreotide therapy with chemotherapy or mTOR inhibitors such as everolimus.